The methodology for X-ray diffraction investigation of icosahedral quasicrystals substructure - Bazdyreva, S.V.; Fedchuk, N.V.; Malykhin, S.V.; Pugachov, A.T.; Reshetnyak, M.V.; Zubarev, E.N. (Functional Materials, 2013)
Method of quantitative estimates of the parameters of the icosahedral quasicrystals substructure, including specific phason defects, developed and successfully worked out using the experimental models of quasicrystalline Al₇₀Pd₂₁Re₉, Ti₄₁.₅Zr₄₁.₅Ni₁₇ and Al₆₄.₅Pd₂₁Mn₁₄.₅ with different preparation technology. The method is based on the analysis of the diffraction lines' width of complete X-ray diffraction pattern. The results are in a good agreement with the prehistory of the samples.